Households’ livelihood diversification and its influencing factors in the Vietnam’s smallholder mixed farming systems - Nam, Le Van; Dung, Nguyen Tien; Hung, Hoang Gia (Asian Journal of Agriculture and Rural Development, 2025)
This study aims to measure the extent of household livelihood diversification, identify its effect on household income, and determine key factors that influence households' livelihood diversification. A total of 426 smallholders were randomly selected for a survey in Hue City, Vietnam, conducted from December 2024 to April 2025. The Simpson Index of Diversity (SID) was used to quantify the extent of livelihood diversification, and a Tobit regression model was applied to determine the determinants of households' livelihood diversification. The findings revealed a moderate level of livelihood diversification (mean SID=0.303), with smallholders engaging in a combination of on-farm, off-farm, and non-farm livelihood strategies. Livelihood diversification was found to have a positive impact on household income. Six factors including age, education level, number of family laborers, number of skilled laborers, participation in credit schemes, and technology adoption were positively and significantly associated with livelihood diversification levels. These results underscore the importance of promoting diversified livelihoods to enhance income and resilience among small-scale households. The study suggests that rural development policies should prioritize human capital development, strengthen access to appropriate technologies, and expand credit opportunities to foster inclusive and sustainable livelihood diversification of smallholders in developing countries.